Age-dependent autophagy induction after injury promotes axon regeneration by limiting NOTCH. Issue 11 (1st November 2020) - Ko, Su-Hyuk; Apple, Ellen C.; Liu, Zhijie; Chen, Lizhen
ABSTRACT: Macroautophagy/autophagy is essential for maintaining cellular homeostasis through the degradation of organelles and proteins. It also has a prominent role in modulating aging. However, the role of autophagy in the neuronal response to axon injury and axon regeneration, particularly in the context of aging, remains largely unknown. Our candidate genetic screen for axon regeneration regulators has identified genes in the autophagy pathway. Using a reporter that monitors autophagosomes and autolysosomes, we were able to monitor the dynamics of autophagy during axon regeneration. In response to axon injury, there was a significant increase in the number of autophagic vesicles. Injury-triggered autophagy activation and axon regeneration capacity undergo an age-dependent decline, and autophagy-activating agents partially rescued these declines. We found that DLK-1 was both required and sufficient for injury-induced autophagy activation. Autophagic vesicles co-localized with the NOTCH4 ortholog, LIN-12 receptor, a previously identified inhibitor of axon regeneration. Epistasis analyses indicate that LIN-12 might be a target of autophagy in axon regeneration. Together, our data suggest that DLK-mediated injury signaling can activate autophagy, which might limit the level of LIN-12 and NOTCH proteins to promote axon regeneration. Our findings reveal that autophagy activation can promote axon regeneration in neurons that lack maximal regrowth capacity, providing a promising therapeutic strategy for axon injury. Abbreviations : 3-MA: 3-methyladenine; ALs: autolysosomes; APs: autophagosomes; ARF-6: ADP-Ribosylation Factor related 6; ATG-9: AuTophaGy (yeast Atg homolog) 9; ATG9A: autophagy related 9A; BA1: bafilomycin A1 ; BEC-1: BEClin (human autophagy) homolog; BECN1: beclin 1; C. elegans: Caenorhabditis elegans ; CEBP-1: C/EBP (CCAAT/enhancer-binding protein) homolog; CNS: central nervous system; DLK-1: Dual-Leucine zipper Kinase; DMSO: dimethyl sulfoxide; DRG: dorsal root ganglion; FOS: Fos proto-oncogene, AP-1 transcription factor subunit; GABA: gamma-aminobutyric acid; GFP: green fluorescent protein; HDA-3: Histone DeAcetylase; IP3: inositol trisphosphate; ITR-1: Inositol Triphosphate Receptor; KLF-2: Kruppel-Like Factor (zinc finger protein) 2; LGG-1: LC3, GABARAP and GATE-16 family; MAK-2: MAP kinase Activated protein Kinase; MAP kinase: mitogen-activated protein kinase; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; MKK-4: mitogen activated protein kinase kinase 4; MTOR: mechanistic target of rapamycin kinase; NGM: nematode growth medium; NICD: Notch intracellular domain; NOTCH: notch receptor; PLM: posterior lateral microtubule; PMK-3: P38 Map kinase family; PNS: peripheral nervous system; SCG10: superior cervical ganglion protein 10; SCI: spinal cord injury; UNC-51: UNCoordinated 51; ULK1: unc-51 like autophagy activating kinase 1; wnd: wallenda